2020
DOI: 10.3390/polym12112625
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stabilization of Gold Nanoparticles Using Water-Soluble Synthetic and Natural Polymers

Abstract: Gold nanoparticles (AuNPs) were synthesized and stabilized using the one-pot method and growth seeding, through utilization of synthetic polymers, including poly(N-vinylpyrrolidone) (PVP), poly(ethylene glycol) (PEG), and poly(vinylcaprolactame) (PVCL), as well as natural polysaccharides, including gellan, welan, pectin, and κ-carrageenan. The absorption spectra, average hydrodynamic size, ζ-potential, and morphology of the gold nanoparticles were evaluated based on various factors, such as polymer concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…The Z potential values obtained for the samples are collected in Table 2 , where it can be seen that the particles carry a negative electrostatic surface charge. This result suggests the involvement of the anionic polysaccharides present in the extract in the stabilization process of the nanoparticles, since the negative values obtained are in accordance with other studies where marine polysaccharides were employed for the synthesis of nanoparticles [ 25 , 26 ]. It is interesting to highlight the values obtained for the nanoparticles synthesized since, according to Z potential guidelines, nanoparticle dispersions with Z potential values ˃±30 mV are highly stable [ 27 ].…”
Section: Resultssupporting
confidence: 90%
“…The Z potential values obtained for the samples are collected in Table 2 , where it can be seen that the particles carry a negative electrostatic surface charge. This result suggests the involvement of the anionic polysaccharides present in the extract in the stabilization process of the nanoparticles, since the negative values obtained are in accordance with other studies where marine polysaccharides were employed for the synthesis of nanoparticles [ 25 , 26 ]. It is interesting to highlight the values obtained for the nanoparticles synthesized since, according to Z potential guidelines, nanoparticle dispersions with Z potential values ˃±30 mV are highly stable [ 27 ].…”
Section: Resultssupporting
confidence: 90%
“…GNP characterization showed that spherical 18 nm GNPs were successfully synthesized and capped with the various ligands [ 37 , 38 ]. Studies have shown that the interaction of GNPs with polymers impacts the size, stability, and distribution of GNPs; therefore, the particle stability was assessed in possible various cell culture conditions [ 38 , 39 ]. The obtained results showed that the particles were stable in cell culture environments allowing for chronic GNP-ligand exposure to the HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Au NP have been successfully synthesized within many natural (e.g., pectin and κ-carrageenan) and synthetic (e.g., poly(N-vinylpyrrolidone) (PVP), PEG, etc.) hydrogels following the in situ method [47]. Incorporation of CP inside a hydrogel can also be achieved by in situ polymerization.…”
Section: (A) (I) Photograph Of Pva/peg Hydrogel (Top) and Pva/peg/go ...mentioning
confidence: 99%